Analisis Kepuasan Masyarakat dan Evaluasi Kinerja Sistem pada Layanan Akta Kelahiran Online Berbasis EUCS+ dan PIECES - Machfud, Syaeful; Prasetia, Okky (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
In the rapidly advancing digital era, the Indonesian government has implemented an online birth certificate service to improve the efficiency and accessibility of public services. This study aims to evaluate both user satisfaction and system performance using two distinct approaches: End User Computing Satisfaction Plus (EUCS+) and Performance Information Economy Control Efficiency Services (PIECES). The EUCS+ model measures user satisfaction based on content, accuracy, format, ease of use, and timeliness, while the PIECES framework assesses system performance from the perspectives of performance, information, economy, control, efficiency, and service. This research employed a quantitative method by distributing questionnaires to 100 respondents who had used the online birth certificate service within the last six months. The results indicate that the highest satisfaction scores were recorded in the dimensions of format (3.81) and ease of use (3.89), whereas system speed and content quality received the lowest scores (2.30 and 2.97, respectively). In the PIECES model, the economy and efficiency dimensions showed strong performance with scores above 3.80, while the control dimension emerged as an area for improvement (2.92). These findings suggest that although the service is relatively effective in terms of visual interface and cost accessibility, significant enhancements are needed in system speed and information quality. This study contributes to a comprehensive evaluation of digital public services and offers recommendations for continuous improvement by government agencies.